Comparative Analysis Between Imam Khomeini and Nurcholish Madjid Thought on Islamic Unity - Ridha, Syaip Muhammad; Fahami, Masoud; Muttaqi, Hossien (Sinergi International Journal of Islamic Studies, 2025)
This study investigates the religious, intellectual, and social dimensions of Islamic unity by examining the contributions of two influential figures: Ayatollah Khomeini, a Twelver Shia leader of the Iranian Islamic Revolution, and Nurcholish Madjid, a Sunni reformist intellectual from Indonesia. Employing Charles Tilly’s 1984 theoretical framework, the research conducts an integrative analysis to identify convergences and divergences in their thought, emphasizing shared values and ideological distinctions. Findings reveal that both scholars advocate for moderation in interfaith and intra-faith engagement, affirming the Qur'an as a foundational text despite interpretive differences. They acknowledge sectarian divisions as historically contingent, often shaped by political forces, yet maintain that Sunni and Shia traditions stem from common Islamic principles. Their perspectives underscore the necessity of unity within the Muslim ummah, particularly in resisting external efforts to exacerbate internal divisions. In conclusion, Khomeini and Madjid exemplify distinct yet complementary approaches to fostering Islamic cohesion. Their shared emphasis on unity, despite theological and cultural differences, offers a valuable paradigm for contemporary discourse. This research affirms the significance of inclusive and integrative thought in promoting solidarity across the global Muslim community.